Droop and Oscillator Based Grid-Forming Converter Controls: A Comparative Performance Analysis - Awal, M. A.; Yu, Hui; Lukic, Srdjan; Husain, Iqbal (Frontiers in Energy Research, 2020)
Two distinct approaches, one droop-based phasor-domain modeled and the other non-linear oscillator-based time-domain modeled, have emerged for the analysis and control of power electronic converters at the system interface layer where these converters are integrating distributed energy resources (DERs). While the droop-type controllers are based on distinct time-scale separation of control loops, purposefully slowing down the response of the DERs, the oscillator-based controllers deliver fast dynamic response with accurate power sharing capability as well as stability guarantee. In this paper, we analyze both the droop- and oscillator-type converters in the context of grid forming converters with respect to steady state terminal response, transient stability, and harmonic compensation in converter output current or in network voltage. Simulation and experimental results are provided to demonstrate the easier implementation of oscillator-based controls that can also achieve supplementary control objectives pertinent to power quality.